Contribute of the MYCOMIX project and future perspectives for Human Biomonitoring and health risk assessment in Portugal - Martins, Carla (2016)
There is a growing concern within public health about mycotoxin involvement in human diseases, namely those related to children. The MycoMix project (2012-2015), funded by the Portuguese Foundation for Science and Technology, gathered a multidisciplinary team aiming at answering several questions: 1) Are Portuguese children exposed daily to one or several mycotoxins through food? 2) Can this co-exposure affect children´s health? and 3) Are there interaction effect between mycotoxins? Mycomix results revealed that Portuguese children (< 3 years old, n=103) are exposed to multiple mycotoxins through food consumption. Cumulative risk assessment results revealed a potential health concern for the high percentiles of intake, specially for aflatoxins which are carcinogenic compounds. This fact assumes particular importance considering the interactive effects found in in vitro bioassays. These results highlight the need for a more accurate approach to assess the human exposure to mycotoxins6. Within the Mycomix project the assessment of mycotoxin exposure was based on calculations combining mycotoxin data in food with population data on food consumption. This approach does not consider some aspects as the inter-individual metabolism variation, the exposure through sources other than food and the heterogeneous distribution of mycotoxins in food. Exposure assessment of mycotoxins in Portuguese population through biomarkers is still missing and further studies are urgent to be developed. The European Human Biomonitoring Initiative (EHBMI), a proposal within the European Joint Programme, aims to advance the understanding of the extent of exposure to environmental chemicals across Europe and the impact on human health, by gathering national expertise in human biomonitoring domain. At national level Mycomix project uncovered the potential health risk of exposure of Portuguese children to multiple mycotoxins. The risk assessment expertise acquired within Mycomix, namely in analysis and toxicology of chemical mixtures, will be brought together as a contribute to EHBMI objectives.